Streamlined approval of biosimilars: moving on from the confirmatory efficacy trial. Issue 11 (November 2020) - Bielsky, Marie-Christine; Cook, Anne; Wallington, Andrea; Exley, Andrew; Kauser, Shahin; Hay, Justin L.; Both, Leonard; Brown, David
Highlights: Licensing of biosimilars promotes wider patient access to essential medicines. Currently, regulators require comparative efficacy trials for complex biosimilars. On review, these trials contribute little additional evidence of biosimilarity. Extensive analytical testing and a pharmacokinetic study are usually sufficient. Abstract : Licensing of biosimilars is essential to promote patient access to 21st-century biological medicines. Regulatory approval of biosimilars is based on the totality of evidence from a head-to-head comparison with reference products (RPs). A clinical efficacy trial is usually required, but this is increasingly questioned. Based on a thorough review of biosimilar applications in the European Union (EU), we conclude that in-depth knowledge of the reference product, allied with high-performing analytical tools, largely predicts clinical comparability, subject to confirmation by a comparative pharmacokinetic (PK) trial. We provide a blueprint for a biosimilar pathway that reduces the need for clinical efficacy trials in exceptional cases, together with qualifying criteria and requirements for streamlined assessment to expedite wider access to affordable biological medicines.